Pengaruh Supervisi Akademik, Budaya Organisasi Dan Motivasi Kerja Guru Terhadap Kompetensi Profesional Guru Sekolah Dasar Negeri - Nurwati, Dian; Bunyamin, Bunyamin; Rasiman, Rasiman (Cetta: Jurnal Ilmu Pendidikan, 2025)
Professional teachers must be able to master learning planning, learning implementation, and evaluation of the learning process. The objectives of the study: 1) to determine the magnitude of the influence of academic supervision on teacher professional competence, 2) to determine the magnitude of the influence of organizational culture on teacher professional competence, 3) to determine the magnitude of the influence of teacher work motivation on teacher professional competence, and. 4) to determine the magnitude of the influence of academic supervision, organizational culture and teacher work motivation together on teacher professional competence. The research approach used is quantitative. This type of research is correlational. The population of the study was 377 teachers and the research sample was 194 teachers. Data collection using a questionnaire. The analysis technique of this study was descriptive data analysis, prerequisite tests including normality tests, multicollinearity tests, heteroscedasticity tests, linearity tests and hypothesis tests including simple and multiple linear regression. The results of the study: 1) The influence of academic supervision has a significant effect on professional competence variables by 80.0%. 2) The influence of organizational culture has a significant effect on professional competence variables by 71.5%. 3) The influence of work motivation has a significant effect on the variable of professional competence by 70.7%. 4) The significant influence of academic supervision, organizational culture and work motivation on teacher professional competence is 82.9%. The conclusion of this study is that there is a significant influence of academic supervision, organizational culture and work motivation on teacher professional competence by 82.9%.